THU0184 Repair of Bone Erosion in Rheumatoid Arthritis by Denosumab: An HR-pQCT Study. (15th July 2016) - Yue, J.; Griffith, J.F.; Shi, L.; Wang, D.F.; Shen, J.; Wong, P.; Li, E.K.; Zhu, T.Y.; Qin, L.; Tam, L.-S.
Abstract : Background: Blockade of receptor activator of nuclear factor kappa B ligand (RANKL), using denosumab retards bone damage in RA. Whether RANKL blockade allows repair of existing bone erosions is so far unclear. Objectives: To compare the reparative effect of denosumab and alendronate on erosions in female RA patients with low bone mass using HR-pQCT. Methods: This is a post-hoc analysis of a randomized-controlled trial. 40 patients with bone erosions were randomized in a 1:1 ratio to receive either subcutaneous denosumab (60mg) once or oral alendronate (70mg) weekly for 6 months. The size of individual bone erosions and the presence and degree of marginal osteosclerosis around the second metacarpophalangeal joint of the non-dominant hand were measured both semi-quantitatively and quantitatively at baseline, 3- and 6-months. Results: At baseline, the mean (±SD) width, depth and volume of the bone erosion were similar for both groups (Table). At 6 months, erosion size significantly decreased in the denosumab group, and significantly increased in the alendronate group. The between group differences in all size criteria were statistically significant at 6 months (all p<0.01). The degree of marginal osteosclerosis was similar between both groups at baseline. At 6-month, more than half of the patients (57.1%) in the alendronate group showed no osteosclerosis (grade 0). In contrast, most patients (80.9%) in the denosumab group showed osteosclerosis (grade 1 or 2). Mean (±SD) pixel attenuation of the erosion margin was similar between both groups at baseline. Mean pixel attenuation was significantly increased at 6 months in the denosumab group though unchanged in the alendronate group. Between group differences for change in mean pixel attenuation between baseline and 6 months were also significant (p<0.05). Conclusions: Bone erosions in RA patients treated with denosumab show evidence of limited repair in contrast to bone erosions in patients treated with alendronate, indicating a favourable impact of RANKL inhibitor on the local bone remodeling. Disclosure of Interest: None declared